A Review of Self-Regulated Strategy Development for Writing for Students with EBD. (February 2014) - Sreckovic, Melissa A.; Common, Eric A.; Knowles, Meagan M.; Lane, Kathleen Lynne
In this systematic review, we evaluated the evidence base of self-regulated strategy development (SRSD; Harris & Graham, 1992) for writing with students with and at risk for emotional or behavioral disorders (EBD). First, we evaluated the quality of studies identified (n = 13) by applying the quality indicators for single case (Horner et al., 2005) and for group (Gersten et al., 2005) design research. Second, we assessed whether SRSD for writing met the standards as an evidence-based practice for students with or at risk for EBD. All articles met 80% or more of the quality indicators (weighted coding range: 6.17–7.00 for single case design; 3.5–4.0 for group design). Results suggested SRSD for writing met standards as an evidence-based practice for this population. The need for future research and implications for practitioners are posed. Limitations and directions for future inquiry are addressed.